IMPROVEMENT OF INVESTMENT ACTIVITIES OF COMMERCIAL BANKS IN THE SECURITIES MARKET - Nafisa Amonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract. This article examines the issues of improving the investment activities of commercial banks in the securities market. Within the framework of the study, the investment strategies of banks and the factors affecting them were analyzed, and the main problems encountered in current practices were identified. The article discusses suggestions for improving investment performance, in particular diversification, risk management, and opportunities to use technological innovations. Recommendations were also developed to make the investment activities of commercial banks in the securities market more effective.